The History of Al-Maturidy Theology In The Volga Region - Adygamov, Ramil (KALAM, 2019)
Al-Maturidy theology has been considered as a traditional creed for many regions in the world, including Volga region of Russia. Throughout the Soviet period, Muslims in Volga were forced to practice their religion in secretive manner, which eventually caused an interruption in the chain of spiritual continuity. But, after the collapse of the Soviet Union, Muslims in Volga started to return to their ethno-confessional tradition. At the same time, the theological tradition had to compete with the Salafi ideology which begun to arrive in the region from abroad. As such has triggered the Muslim proponents of Maturidy traditions to reclaim their heritage. This study aims at tracing the historical process of the origin and development of Maturidy thought in the Volga-Ural region. It uses descriptive and comparative methods and the theory of continuity and changes. Observing the chronological sequence, the study traces the process of the origin and development of Maturidy ideology. The chronological scope of this study is limited by the period from the tenth century until our time. The study reveals that the al-Maturidy's teachings in the region for all periods of historical development have experienced five periods. Three periods show a rapid development stage and two periods experience a decline.